2015
DOI: 10.1049/iet-rpg.2014.0175
|View full text |Cite
|
Sign up to set email alerts
|

Operational characteristics of hybrid‐powered three‐phase induction motor via synchronous and photovoltaic generators with MPPT utilised by synchronous generator automatic voltage regulator

Abstract: The operational characteristics of a stand-alone hybrid-powered system are investigated. The sources are conventionally powered synchronous generator and photovoltaic (PV) array. The voltage of the common coupling point is controlled by the automatic voltage regulator of the synchronous generator via which the maximum power point (MPP) of the PV generator is tracked using the open-circuit voltage method. Numerical simulations based on the non-linear dynamical model in dq stationary reference frame are conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As can be noted from Figure 1, the output voltage as function of the current of the PV generator is highly nonlinear. It has been approximated using a 10th order polynomial function as (Widyan, 2015a(Widyan, , 2015bWidyan, 2014;Sweidan, 2017;Sweidan and Widyan, 2017):…”
Section: Pv Design and Output Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be noted from Figure 1, the output voltage as function of the current of the PV generator is highly nonlinear. It has been approximated using a 10th order polynomial function as (Widyan, 2015a(Widyan, , 2015bWidyan, 2014;Sweidan, 2017;Sweidan and Widyan, 2017):…”
Section: Pv Design and Output Characteristicsmentioning
confidence: 99%
“…It is concluded that the system is reliable and can tolerate different disturbances as it can settle down to the normal operating points. The operational characteristics of a hybrid powered three-phase induction motor by PV and synchronous generator is carried out (Widyan, 2015b). The voltage of a common coupling point is controlled by the AVR of synchronous generator which is used to change its magnitude in accordance with the MPP of photovoltaic (PV) generator at all convenient intensity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the proper control of PV panel is necessary to optimise its output power, and hence the use of maximum power point tracking (MPPT) controller with PV system is essential to make it as a stable electrical energy source and to provide maximum output power at all irradiance levels and environmental conditions. The large number of maximum power tracking techniques have been utilised in different solar PV energy-based applications [1][2][3][4][5]. The proposed water pumping system utilises perturbation and observe (P&O) algorithm for PV power optimisation, because of its less implementation complexity and independency from the PV array parameters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the nonlinear characteristics of the PV array [1], various MPPT methods have been designed. Among them, there are several widely applied MPPT methods, such as the perturb and observe (P&O) methods [2–9], incremental conductance (INC) methods [10–14], ripple correlation control (RCC) methods [15–17], and open or short circuit methods [18–20]. The basic idea of P&O method is to move the panel power to the maximum power point (MPP) by continuously perturbing and observing the panel operation point.…”
Section: Introductionmentioning
confidence: 99%